2022
DOI: 10.1002/chem.202201659
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Extra‐Framework Cations in Faujasite Zeolites for Capture of Trace Carbon Dioxide

Abstract: The development of cost-effective sorbents for direct capture of trace CO 2 (< 1 %) from the atmosphere is an important and challenging task. Natural or commercial zeolites are promising sorbents, but their performance in adsorption of trace CO 2 has been poorly explored to date. A systematic study on capture of trace CO 2 by commercial faujasite zeolites reveals that the extra-framework cations play a key role on their performance. Under dry conditions, BaÀ X displays high dynamic uptake of 1.79 and 0.69 mmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Both Ca‐LTA‐3 and Mn‐LTA‐3 display high DAC capacity and good cyclic DAC performance. Notably, Ca‐LTA‐3 exhibits the highest DAC capacity (1.2 mmol/g, Figure 5B,D) among the reported DAC physisorbents in the open literature to the best of our knowledge 8,9,22,25,26,38,74 . Thanks to the superior DAC capacity and fast kinetics (evidenced by the sharp breakthrough curve, Figure 5A,C), one gram of Ca‐LTA‐3 is able to thoroughly remove the CO 2 in around 80 L of “dry” air at room temperature and atmospheric pressure 6,75 …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Both Ca‐LTA‐3 and Mn‐LTA‐3 display high DAC capacity and good cyclic DAC performance. Notably, Ca‐LTA‐3 exhibits the highest DAC capacity (1.2 mmol/g, Figure 5B,D) among the reported DAC physisorbents in the open literature to the best of our knowledge 8,9,22,25,26,38,74 . Thanks to the superior DAC capacity and fast kinetics (evidenced by the sharp breakthrough curve, Figure 5A,C), one gram of Ca‐LTA‐3 is able to thoroughly remove the CO 2 in around 80 L of “dry” air at room temperature and atmospheric pressure 6,75 …”
Section: Resultsmentioning
confidence: 91%
“…The CO 2 concentration in the "dry" air was measured to be 350 ppm, and the sorbents in the open literature to the best of our knowledge. 8,9,22,25,26,38,74 Thanks to the superior DAC capacity and fast kinetics (evidenced by the sharp breakthrough curve, Figure 5A,C), one gram of Ca-LTA-3 is able to thoroughly remove the CO 2 in around 80 L of "dry" air at room temperature and atmospheric pressure. 6,75 Comparing the DAC capacity measured by breakthrough adsorption with the ideal CO 2 adsorption capacity measured using singlecomponent adsorption at the same condition (at 25 C, using the adsorbents activated at 300 C) shows that the DAC capacity (Ca-LTA-3: 0.76 mmol/g, Mn-LTA-3: 0.24 mmol/g, Figures 5B) is slightly lower than the ideal CO 2 capacity (Ca-LTA-3: 1.12 mmol/g, Mn-LTA-3: 0.35 mmol/g, at 298 K, 0.04 kPa, Figure 1E).…”
Section: Dac In "Dry" Airmentioning
confidence: 99%
“…In the TVSA system, a vacuum pump will generate 0.1 bar vacuum to desorb CO 2 from the 13X bed with the increased bed temperature at 125 °C. Use of different frameworks and exchanged cations in zeolites will likely allow further improvement of the cold-temperature DAC process by increasing the CO 2 uptake and/or selectivity over N 2 and/or water. , Therefore, subsequent research should focus on cold-temperature DAC operations using zeolites with various frameworks and cation-exchanged forms.…”
Section: Resultsmentioning
confidence: 99%
“…[31,32] The influence of Sr 2+ cations on the aluminum distribution in the chabazite framework and crystallization rate was investigated recently, revealing that the synthesis time could be reduced from weeks to hours. [33] Among the available literature, it has been reported that calcium-or barium-exchanged Xtype faujasites and chabazites exhibit better adsorption capacity at very low CO 2 pressures, [34,35] yet a higher N 2 capacity was also observed for barium-exchanged X-type faujasites and chabazites at low pressures (<30 kPa). [26,36] In order to investigate the changes on both the synthesis and adsorption properties of nanozeolites prepared in the presence of alkaline-earth metal cations, we considered the chabazite framework because it exhibits a high adsorption capacity, and depending on the type of extra-framework cations present, a high selectivity toward CO 2 over CH 4 or N 2 .…”
Section: Introductionmentioning
confidence: 99%